Effect of compost/water ratio on some main parameter of compost solutions - Kiss, Nikolett Eva; Gorliczay, Edit; Nagy, Péter Tamás; Tamás, János (Acta Agraria Debreceniensis, 2021)
Composting is an efficient technology for the utilisation of by-products and waste. It is also suitable for treating raw materials to convert fertilisers that are not recommended for application without pre-processing. Such is the case with poultry manure, which is very important to pre-treat due to its hazardous properties. An increasingly common form of compost is compost tea, which is made by soaking compost in water. In our experiment, we made compost tea from a composted and granulated poultry manure product. Three mixing ratios were used (1/5, 1/10, 1/10) and compost teas were set for three different extraction times (24–48–72 hours). After elimination of the experiment, the pH, EC, and nitrate and ammonium contents of the samples were measured. The aim of this study was to determine whether there is a difference between each mixing ratio and different extraction times. Based on our results, it can be said that the fluctuation of pH values during the experiment was low. Regardless of the mixing ratio and extraction time, the samples were in the slightly acidic range. The electrical conductivity, nitrate and ammonium content follow a similar trend, the values decrease significantly with the increase of the mixing ratio. Similar tendency was observed at the incubation time. The concentrations of both EC and nitrogen forms increase with increasing incubation time, in most cases significantly.